Word images : new perspectives on Canícula and other works by Norma Elia Cantú - Herrera-Sobek, María; Gutierrez y Muhs, Gabriella (The University of Arizona Press, 2017)
This collection of critical essays unveils for the first time Norma Elia Cantú's contribution as a folklorist, writer, scholar, and teacher. Word Images unites two valuable ways to view and use Cantú's work: Part 1 comprises essays that individually examine Cantú's oeuvre through critical analysis. Part 2 is dedicated to ideas and techniques to improve the use of this literature by teachers and professors, with a particular focus on tools for using Canícula. Contributors: Steven W. Bender Aurora Chang Vanessa Fonseca Gabriella Gutiérrez y Muhs María Herrera-Sobek Ellen McCracken María Esther Quintana Millamoto Aldo Ulisses Reséndiz Ramírez Rose Rodríguez-Rabin Jesús Rosales Carlos Sibaja García María Socorro Tabuenca Juan Velasco